Mitochondria associated membranes in dilated cardiomyopathy: connecting pathogenesis and cellular dysfunction - He, Pingge; Chang, Hongbo; Qiu, Yueqing; Wang, Zhentao (Frontiers in Cardiovascular Medicine, 2025)
Dilated cardiomyopathy (DCM) is a leading cause of heart failure, yet therapeutic options remain limited. While traditional research has focused on mechanisms such as energy deficits and calcium dysregulation, increasing evidence suggests that mitochondria-associated membranes (MAMs) could provide new insights into understanding and treating DCM. In this narrative review, we summarize the key role of MAMs, crucial endoplasmic reticulum (ER)-mitochondria interfaces, in regulating cellular processes such as calcium homeostasis, lipid metabolism, and mitochondrial dynamics. Disruption of MAMs function may initiate pathological cascades, including ER stress, inflammation, and cell death. These disruptions in MAM function lead to further destabilization of cellular homeostasis. Identifying MAMs as key modulators of cardiac health may provide novel insights for early diagnosis and targeted therapies in DCM.